Development of Ambient Cured High-Strength Fiber Reinforced Geopolymer Composites - Khan, Musaad Zaheer Nazir (Curtin University, 2018)
This research focused on the development of high-strength and ductile geopolymer composites cured in ambient conditions, followed by characterization of the material properties under quasi-static, dynamic, and multiaxial stress conditions. The research findings encourage using geopolymer materials in actual constructions and applications requiring high-energy absorption capacity. The research data also provides significant input for developing the corresponding material model for predicting the behaviour of structures made of geopolymer materials subjected to static and dynamic loads.